Exploring the Use of Natural-Material Media in Indonesian Language Learning to Enhance Children’s Creativity - Suprihatien Suprihatien; Elsa Wahyu Ningrum (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study explores how the use of natural-material media enhances children’s creativity and linguistic expression in Indonesian language learning. Employing a qualitative phenomenological approach, data were collected through classroom observations, student interviews, and documentation of creative language and art artifacts. The findings reveal that natural materials—such as leaves, twigs, stones, and sand—serve as effective learning media that stimulate sensory engagement, imagination, and collaboration. Students demonstrated higher levels of originality, persistence, and expressive language use when describing and narrating their creations compared to conventional classroom activities. These nature-based experiences fostered intrinsic motivation and emotional engagement, reflecting the principles of Self-Determination Theory and Csikszentmihalyi’s concept of flow. The study also supports constructivist and sociocultural learning perspectives, showing that creative interaction with natural materials enables students to construct meaning actively and collaboratively. Moreover, the activities promoted ecological awareness and empathy, aligning with the goals of Education for Sustainable Development (ESD). The integration of natural-material media in Indonesian language learning thus provides a holistic educational experience that unites cognitive, emotional, linguistic, and ecological dimensions. Educators are encouraged to adopt nature-based strategies to cultivate creativity, imagination, and environmental consciousness, creating meaningful language learning experiences rooted in both culture and nature.